A robust potency assay highlights significant donor variation of human mesenchymal stem/progenitor cell immune modulatory capacity and extended radio-resistance. Issue 1 (December 2015) - Ketterl, Nina; Brachtl, Gabriele; Schuh, Cornelia; Bieback, Karen; Schallmoser, Katharina; Reinisch, Andreas; Strunk, Dirk
Abstract The inherent immunomodulatory capacity of mesenchymal stem/progenitor cells (MSPCs) encouraged initiation of multiple clinical trials. Release criteria for therapeutic MSPCs cover identity, purity and safety but appropriate potency assessment is often missing. Reports on functional heterogeneity of MSPCs created additional uncertainty regarding donor and organ/source selection. We established a robust immunomodulation potency assay based on pooling responder leukocytes to minimize individual immune response variability. Comparing various MSPCs revealed significant potency inconsistency and generally diminished allo-immunosuppression compared to dose-dependent inhibition of mitogenesis. Gamma-irradiation to block unintended MSPC proliferation did not prohibit chondrogenesis and osteogenesis in vivo, indicating the need for alternative safety strategies.